Tuberkulosis Limfadenopati Paraaorta Abdomen pada Pasien Pasca Infeksi Covid-19: Sebuah Laporan Kasus - Cecep Kurnia Suhayat; Nico Leonardy; Wardah Hanifah; Anita Chatrin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
COVID-19 and tuberculosis (TB) remain major public health challenges in Indonesia, where the COVID-19 pandemic has disrupted TB prevention and control efforts, leading to decreased detection rates and increased mortality. Considering the coexistence of COVID-19 and TB in high-burden populations and the occurrence of post-COVID-19 tuberculosis cases, this report explores the potential activation of latent TB following COVID-19 infection. A 21-year-old female tested positive for SARS-CoV-2 by real-time PCR and was treated for COVID-19. Four weeks later, she developed persistent dry cough, epigastric discomfort, and night sweats. Radiological and hematological examinations revealed ground-glass opacities, lymphadenopathy, elevated inflammatory markers, and anemia. A positive IGRA test and paraaortic lymph node involvement confirmed extrapulmonary TB. The patient received nine months of antituberculosis therapy, resulting in complete resolution of lymphadenopathy. This case highlights a possible link between COVID-19 infection and the reactivation of latent TB, potentially triggered by immune dysregulation, cytokine storms, or T-cell depletion associated with SARS-CoV-2 infection. Clinicians should consider TB screening for post-COVID-19 patients exhibiting persistent or unexplained symptoms, particularly in TB-endemic regions, as early detection and treatment are essential to prevent severe complications and community transmission.